HISTORY IN THE MIRROR OF CHILDREN'S LITERATURE - Schupplerova, Stanislava (Bohemica Olomucensia, 2020)
The article focuses on ways of depicting history and historical events in Czech prose dedicated to children. Specifically, these are two books that return thematically to the period of the First Republic. We are interested in how the authors work with the chosen topic and narrative strategies, not only at the level of the text, but also the image.
Keywords: Czech literature; prose; history; children's literature; narratology